REDES DE COOPERAÇÃO INTERORGANIZACIONAL E O PAPEL DAS ENTIDADES DE APOIO: ESTUDO DE CASO DA FEIRA DO PRODUTOR DE GUARAPUAVA - PETTERSON, ANDRÉ REZENDE (2016)
This present study approached the field of relationships that occur in the context of inter-organizational networks that receive government support. The goal of research is to understand the relationship between support organizations and small rural family enterprises, participants from the producer fair, called “feira do produtor”, held in the city of Guarapuava, central region of Parana state. This fair is an event that has about 120 fair dealers, who are farmers and urban. It was created by initiative of the municipal office of agriculture in its early stages coordinating all activities. Currently, the fair dealers are members of an independent association, created especially to coordinate the event. The choice of theme is justified by the lack of publications in cases of operational dependence on small rural entrepreneurs networks in relation to their supporters. Thus, approached initially the origin of studies on networks, their types, relationships, cooperation, approaches to the study of networks and rural family enterprises. To achieve the goals, it adopted the case study as a research strategy, being the producer of the fair the object of study, focusing on their relationships. Understanding the phenomenon occurred inductively, by combining quantitative and qualitative methods. The quantitative research tool for application resulted in the construction of a representative network sociogram that with the help of UCINET © software, it was possible to map the structure of relations between actors in the “feira do produtor”. Using the content analysis of the reports of texts, interviews transcription and field observations, described the transactional content network. The analysis of the relationship between the fair and the main support entity concluded that: i) the fair producer is inextricably linked to its creators government; ii) government actors are privileged in terms of centrality and potential to access the network; iii) the influence of governmental actors on the fair dealers is inversely proportional to the time of work at the fair; iv) government actors are bridges that connect the fair dealers to external domains; v) the flow of information that feeds the network is associated with the internal structure; vi) the network is dense, with favorable indications of cohesion and connectivity, facilitating the free flow of information; vii) the content of the information circulating on the network is considered important by fair dealers for business at the fair. These findings allowed the researcher to recommend that the fair as network level maintains a close relationship with your government supporter, seeking to strengthen internally through the construction of a structure of leadership that gives you stability.